Correlation between endometrial thickness and histopathological report in patients with abnormal uterine bleeding: a prospective study - Lewis, Preeti F.; Gupta, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) refers to any bleeding from the uterus that is irregular in volume, duration, or frequency and does not fall within the normal menstrual cycle pattern. The objective of this study was to find the correlation between endometrial thickness on transvaginal or transabdominal ultrasound with histopathological assessment of the endometrial assessment on Dilatation and curettage in patients with AUB. Methods: It was a prospective Cohort study. A total of 102 women in reproductive and peri-menopausal age (taking inclusion and exclusion criteria into account) who underwent dilatation and curettage for abnormal uterine bleeding during the period March 2023- March 2024 were taken and analysed and correlated their HPR reports with their endometrial thickness measured with ultrasound. Results: Mean age of patients was 37.83±9.43. Mean endometrial thickness (mm) was 9.15±3.474. For pathological abnormalities in ultrasonography the cutoff point that delineates the abnormal histology and normal histology for endometrial thickness was 14.50 mm area under the curve (AUC) was 0.783 and sensitivity, specificity of 100%, 70% respectively. Conclusions: A positive correlation between endometrial thickness and histopathological findings was observed, underscoring the importance of endometrial evaluation in patients presenting with abnormal uterine bleeding.